IMPLEMENTASI PENDEKATAN FUNGSIONAL DALAM PEMBELAJARAN BAHASA ARAB MELALUI METODE COMMUNITY LANGUAGE LEARNING - Hanum, Syarifah; Rahmawati, Rahmawati (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2019)
This study aims to explain and describe the implementation of functional approaches in learning Arabic through the method of community language learning. Community language learning method is a method that aims for students to learn to use language that is learned communicatively. Community language learning (CLL) is the name of a method developed by Charles A Curran and his colleagues. Community language learning (CLL) is often used in communicative learning or speaking skills. research in this study is the Research field. Collecting data in this study is qualitative (not in the form of numbers) through a review of some literature and using qualitative analysis in the presentation of data, data analysis and conclusion. The results of his research are detailed descriptions and explanations of the details of Arabic learning instruments that use the community language learning method in terms of a functional approach to realize the goals of modern Arabic learning, namely factual communication, in the sense that students are able to function foreign languages learned as communication tools, in this case Arabic.